The influence of cultural origins of visitors when staying in the city that never sleeps - Moro, S.; Rita, P.; Ramos, P.; Esmerado, J. (Tourism Recreation Research, 2022)
Smart tourism can benefit from Big Data to offer personalized services that better meet tourist demands. This study addresses the adaptation versus globalization debate by analyzing all reviews made about New York City (NYC) on Booking.com, a total of 115,297 reviews for 307 hotels. The collected dataset was divided into 10 cultural clusters and category of each hotel by the star rank system. Then, 5 categories were analyzed: cleanliness, food, location, price, and staff. Results showed both divergent and convergent opinions about the accommodation offer of NYC, depending on the selected category. Food and staff gathered different opinions among the 10 cultural clusters. Particularly, cultures less subjected to globalization tend to write more negative reviews about food. Also, cultures with a higher distance in treatment between tourists and staff such as Confucian, South-East Asia and Middle-Easterners, appreciate less the egalitarian treatment of NYC hotel staff.